Vadon, Lehel. Az amerikai irodalom és irodalomtudomány bibliográfiája Magyarországon 2000-ig [A Bibliography of American Literature and Literary Scholarship in Hungary to 2000]. Eger: EKTF Líceum, 2007. 3 volumes. Vol. I: 1275 pp; Vol. II: 1138 pp; Vol. III: 1243 pp. - Vöő, Gabriella (FOCUS: Papers in English Literary and Cultural Studies, 2024)
Some reference books can be read for both business and pleasure. Readers who are curious about American literature and literary scholarship and consult any of the three volumes of Lehel Vadon’s impressive bibliography also embark on an enjoyable imaginary travel through time. These new volumes continue and extend time. Lehel Vadon’s previously published bibliographical works on American literature and literary scholarship,' and the massive volumes offer a unique opportunity to explore the interests and preferences of our predecessors, translators, and literary scholars alike, in mediating, surveying, and critically evaluating American literature in Hungary. The adventurous browser will have moments of elation seeing the rich and almost instantaneous translation and critical acclaim of Mark Twain’s work, but may also feel embarrassment at the rather late reception of Henry James. S/he may acknowledge the richness of primary and critical sources of Charles Olson, but regret the scarcity of critical articles on Hart Crane.